The importance of using Anglophone literature in high school English classes - OLIVEIRA, Arielly Azevedo de (2023)
This paper aims to discuss the importance of using Anglophone literature in high school English language classes. A brief presentation of Edgar Allan Poe's short story “The Black Cat” (1843) will be made, this short story falls into the category of Gothic tale, and addresses a theme that is seen as interesting to students, since bringing horror stories and mysteries into the classroom sharpens their thoughts and intrigues them. In this way, we also thought of an application proposal, with two sequences of lesson plans with this genre, since its use allows students to think about the actions presented in the short story, allowing them to develop their critical sense and expand their linguistic, discursive, and cultural knowledge. For the discussion of this paper, we will bring authors such as Tzvetan Todorov (2010), philosopher and linguist, who has produced several works in the field of linguistic research and literary theory, and Richard Beach (2011), researcher of secondary teaching methods in English language arts, with particular emphasis on the teaching of literature.